Da sombra da magnólia ao porvir do Grupo Escolar Governador Clóvis Salgado de 1956 a 1971 - Bezerra, Luciene Teresinha de Souza (2016)
From 1950s through 1970s, political changes have had severe impacts on public education in Brazil, especially the change from democratic government to military rule. In this process of change, public education not only became devoid of state resources but also turned into a subject of an intense debate on how it should be: if public, if private. As an outcome of the debate, the first Brazilian education guidelines law has translated into it much of the privatist aspirations; since 1964, it served military rule’s plans to legitimize his government. This study puts in that historical context its intention of writing part of the history of Grupo Escolar Governador Clóvis Salgado, located in Ituiutaba, MG. The study started from the premise of contradiction between high economic rates and illiteracy rates also raised to build an understanding of concepts, practices, methods and educational content present in this school; of the profile of teachers and students; of the relationship between economy, illiteracy and graduated school. The research aimed to understand migration from country to town and from Northeast to Triângulo Mineiro region as causes of urban population growth, to grasp the struggle for control of education and to understand educational practices in times of democracy and of dictatorship. As sources, this drew from laws, chamber of councilors’ minutes, newspapers and magazines, oral accounts, class record books, school reports, photographs and statistic data. Results reaffirm the consensus of lack of school funding in local strategies to raise funds (community fundraising campaigns by school parties, raffles and bazaars). They pint out local political action — from the City Hall — in favor of state schools, as well as the volunteer work of professionals like doctors. The work of teachers and principal went beyond pedagogical and administrative duties, since they had to take responsibility for the full support of the school. It is as if these conditions translated in practice both requirements of an educational law unaware of the social and educational reality of the majority and the political attitude attentive to social reality but not to the public education.